1980
DOI: 10.1093/carcin/1.10.871
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of benzo[a]pyrene by a human hepatoma cell line

Abstract: The liver-derived human cell line, Hep G2, has high benzo[a]pyrene-metabolizing activity and converts benzo[a]pyrene to intermediates that are mutagenic and that bind to DNA. This cell line will be useful for studying metabolic activation of polycyclic aromatic hydrocarbons and other xenobiotics by human tissue and as an activation system in short-term screening assays for identifying compounds with carcinogenic potential for humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…Aryl sulfatase had no effect on radioactivity. These results suggested that this human liver tumor cell line does not extensively utilize the phenol detoxification pathway (Diamond et al 1980). increased, the ratio of dihydrodiol/phenolic metabolites also increased.…”
Section: Health Effectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Aryl sulfatase had no effect on radioactivity. These results suggested that this human liver tumor cell line does not extensively utilize the phenol detoxification pathway (Diamond et al 1980). increased, the ratio of dihydrodiol/phenolic metabolites also increased.…”
Section: Health Effectsmentioning
confidence: 95%
“…A human hepatoma cell line (HepG2) has high benzo[a]pyrene-metabolizing activity and converts benzo[a]pyrene to metabolites (Diamond et al 1980 proportions of 3-hydroxybenzo[a]pyrene and the parent compound were much higher than in the medium. Conversely, the proportion of water-soluble metabolites in the cell lysate was lower than in the medium.…”
Section: Health Effectsmentioning
confidence: 99%
“…[17][18][19][20][21] These cell lines were maintained in Dulbecco's modified essential medium (DMEM; Sigma Chemical Co., St. Louis, MO) supplemented with 10% heat-inactivated fetal bovine serum (Atlanta Biologicals, Norcross, GA) in a humidified incubator at 37°C in 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
“…Certain cell lines, including Hep G2, Hep 3B and SKHep-l, can carry out cytochrome P-450-dependent mixed function oxidase (MFO) and conjugation reactions [1][2][3][4] and are capable of activating benzo(a)pyrene, aflatoxin B~ and cyclophosphamide to cytotoxic and mutagenic metabolites [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%